2012
DOI: 10.1084/jem.20121069
|View full text |Cite
|
Sign up to set email alerts
|

The intramembrane protease SPPL2a promotes B cell development and controls endosomal traffic by cleavage of the invariant chain

Abstract: The intramembrane protease SPPL2a cleaves the NTF of invariant chain (CD74), which is essential for normal trafficking of MHC class II–containing endosomes and thus for B cell development and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
203
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(212 citation statements)
references
References 59 publications
9
203
0
Order By: Relevance
“…Major phenotypic findings described in this study were additionally confirmed in two SPPL2a mutant mouse lines (19,20). Additional ablation of CD74 in SPPL2a 2/2 mice improved B cell maturation and function, indicating that the B cell phenotype of these mice can be mainly ascribed to the incomplete turnover of the CD74 NTF (13). In SPPL2a 2/2 B cells, the unprocessed CD74 NTF accumulates in endosomal compartments where it disturbs membrane trafficking, leading to a highly increased abundance of endosome-derived vacuoles in these cells.…”
supporting
confidence: 72%
See 3 more Smart Citations
“…Major phenotypic findings described in this study were additionally confirmed in two SPPL2a mutant mouse lines (19,20). Additional ablation of CD74 in SPPL2a 2/2 mice improved B cell maturation and function, indicating that the B cell phenotype of these mice can be mainly ascribed to the incomplete turnover of the CD74 NTF (13). In SPPL2a 2/2 B cells, the unprocessed CD74 NTF accumulates in endosomal compartments where it disturbs membrane trafficking, leading to a highly increased abundance of endosome-derived vacuoles in these cells.…”
supporting
confidence: 72%
“…Generation of SPPL2a 2/2 mice has been described previously (13). Mice used in this study were backcrossed for 10 generations on a C57BL/6N Crl background.…”
Section: Mouse Strainsmentioning
confidence: 99%
See 2 more Smart Citations
“…This requires cathepsin S (Riese et al 1996;Driessen et al 1999;Nakagawa et al 1999;Shi et al 1999) or cathepsins L and F (Nakagawa et al 1998;Shi et al 2000), depending on the cell type. Degradation of the remaining transmembrane fragment requires the intramembrane endopeptidase SPPL2A (Beisner et al 2013;Bergmann et al 2013;Schneppenheim et al 2013). Although early studies proposed that Ii degradation is regulated and enhanced in response to DC activation (Pierre and Mellman 1998), subsequent studies proved that Ii processing is a constitutive process and not rate limiting for antigen presentation by MHCII (Villadangos et al 2001(Villadangos et al , 2005El-Sukkari et al 2003;ten Broeke et al 2010).…”
Section: Biosynthesis Of Mhciimentioning
confidence: 99%